“E-fatwā” a comparative analysis of islamonline and islam q&a - Yusuf, Badmas Abdulhameed; Ghalia, Bouhedda (IIUM Press, International Islamic University Malaysia, 2017)
Sequel to scientific and technological evolutions, electronic fatwā i.e. e-fatwā has become a phenomenon among means of fatwā dissemination in the contemporary world. Arguably, it has become the easiest means of getting fatwā as a response to various life challenges, notwithstanding the geographical factor. Day by day, the number of websites devoted for fatwā making purpose has been increasing astronomically. While such means greatly assists in Daʿwah outreach, the negative aspect i.e. distortion of Islamic teachings could not be overlooked. Against this backdrop, this work undertakes a study of e-fatwā within four chapters. Chapter One is composed of introductory remarks and other preliminary information about the work. Chapter Two elaborates on the concept of e-fatwā, its significance in dissemination of Islamic teachings, as well as the prerequisites of both muftī and mustaftī. Chapter Three focuses on the comparative analysis of case study sites i.e. Islamonline and IslamQ&A with a view to highlighting some merits and demerits of e-fatwā. In pursuance of this, a number of fatāwā from the case study sites in four major aspects, namely, Ritual, Matrimonial, Financial and Bio-Medical are considered. While Chapter Four presents the findings of the study with some recommendations deemed necessary for proper utilization of e-fatwā in view of its overriding impacts on Muslim daily life. The study adopts both analytical and comparative methods. The former method is used for the purpose of expatiating on the basic concepts of the study, essential ingredients of a correct e- fatwā, and for the explanation of the selected fatāwā from both sites. Whereas the latter method is employed for the comparative analysis of those fatāwā vis -a –vis their merits and demerits. Lastly, findings of the study and recommendations for proper use of electronic means for the purpose of fatwā making, are stated.